Emerging Economies' versus Advanced Countries' Investment Impact in Africa - Ezemenari, Kene (World Bank, Washington, DC, 2017)
This paper provides evidence on the labor productivity growth and employment impacts of foreign direct investment in selected countries in Africa over the years 2001-2012. It uses data from five emerging economies (Brazil, Russia, India, China, and South Africa) and advanced countries (Canada, France, Germany, Italy, Japan, the United Kingdom, and the United States of America). The estimation, using system generalized method of moments, shows that foreign direct investment from emerging economies and advanced countries has increased labor productivity growth and employment in Africa, when human capital and governance are controlled for. However, the level of impact varies based on the origin of investment.